Atypical presentation of primary Ewing's sarcoma - Nancy V Jeniffer; Arpitha Panduranga; B P Karunakara (Indian Journal of Medical and Paediatric Oncology)
Ewing's sarcoma is the second most common bone tumor in children and adolescents. Its annual incidence is 0.6/million total population worldwide, and in some populations in India, its incidence can account for 15%–19.4% of the primary bone tumors. Ewing's sarcoma is a highly malignant round cell tumor, affecting the metadiaphyseal and the diaphyseal regions of the long bones. Spine involvement, as a primary focus in Ewings sarcoma is uncommon, but when present, usually affects the sacrum. Origin from non sacral region is extremely rare. We report a case of acute onset of paraplegia progressing to quadriplegia in a child with metastatic involvement of the spine, primary focus being the nonsacral spine which is inherently challenging to an early diagnosis. Ewing's sarcoma though has improved survival with chemotherapy and radiotherapy, primary spine focus has poor prognosis.